Development of the Alberta facial clinical evaluation scale: A patient‐centred outcomes instrument for facial nerve paralysis. (8th October 2019) - Hamour, Amr F.; Mendez, Adrian I.; Biron, Vincent L.; Seemann, Robert; Ansari, Kal; Liu, Richard; Seikaly, Hadi; Côté, David W. J.
Abstract: Objectives: Facial nerve paralysis has functional, psychological and social consequences for patients. Traditionally, outcome measurements for facial nerve injuries have been clinician derived. Recent literature has shown that patient perspective is valuable and necessary in outcomes research. This study aimed to identify patient domains of concern and subsequently, develop a point‐of‐care questionnaire for clinical use. Design: This mixed‐methods prospective study was completed in three phases. In Phase I, 15 facial nerve injury patients were interviewed individually. Interviews were digitally recorded, transcribed and coded with NVivo software. Analysis led to a conceptual framework detailing the most important quality of life outcomes. During Phase II, a focus group was held with five new patients in order to prioritise the outcome themes to a top six list. A second focus group was held with Otolaryngology‐Head and Neck staff surgeons to create a 25‐item questionnaire based on these six themes. In Phase III, the questionnaire was administered to 10 new patients to test for comprehension. Setting: University of Alberta Hospital, Edmonton, Alberta, Canada. Participants: A total of 30 patients with facial nerve injury were included in the various phases in the study. In addition, 5 staff Otolaryngology‐Head and Neck surgeons participated as focus group contributors. Main outcome measures: Domains of concern and quality of life outcomes as reported by facial nerve injury patients. Results: Patients identified a total of 16 themes encompassing both functional and psychological deficits related to their facial nerve injury. From these findings, a 25‐item Likert‐type scale, the A‐FaCE scale, was developed for clinical use. Conclusions: Patients with facial nerve paralysis experience functional and psychological deficits. This study led to the creation of the first patient‐reported instrument for this population that addresses functional impairment, social function, psychological well‐being and self‐perception of appearance.